An Analysis Of Students Ability In Writing Descriptive Texts At The Ninth Grade Of Smpit Sabbihisma Padang - Christina, Dian; Putri, Dwi Megista (Jurnal Pendidikan Tambusai, 2021)
The research was conducted aiming to an analysis of students’ ability in writing descriptive texts at the ninth grade of SMPIT Sabbihisma Padang. The method used in this research is the qualitative method. The subjects of this study were the 32 students of the IX-1 class. The research investigated the descriptive writing text which had been done by the ninth-grade students of SMPIT Sabbihisma Padang. The researcher analyzed the students’ writing results referring to the five aspects. They were organization ideas, developed ideas, grammar, vocabulary, and mechanics. After analyzing the texts written by the student, the researcher categorizes them into four categories, namely excellent, good, fair, and poor. The result is 1 student or 3, 13%, there are 6 students or 18, 75%, there are 3 students or 9, 37%, and there are 22 students or 68, 75%. The average students’ capability in writing descriptive text is poor. The problems faced are (1) the students have problems with the limited number of vocabulary, (2) developing the idea in a descriptive text, (3) grammar mastery. Grammar mastery is the most problem faced by the students. The causes of the problem are (1) students’ low motivation, (2) Understanding.